KOMIK RAMAYANA KARYA R.A. KOSASIH: SIKLUS KEHIDUPAN SPRITUAL SRI RAMA DAN DEWI SINTA - Saksono Prijanto (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
Unlike the Mahabharata story that featured the “gray” characters, the story of Ramayana is more revealing the “black and white” characters. Through out hundreds of pages, readers witness the action of Sri Rama, Lakshmana and Hanoman in an effort to free the Goddess Sinta from Ravana‟s in solence. The story of Sri Rama is very important because it has a high value, especially in the ethical teachings that in all parts of the story that is internalized. Mean while, the go alof this study is to reconstruct the spiritual life cycle of Sri Rama and Sinta Dewi.To achieve that goal is used methods or semiotic approach. Its application of this semiotic and the theory of functional model such as actants with its chart (narrative syntax) of Greimas. Mean while, the result is that the comic Ramayan are veals the problems of humanity (truth, courage, and chastity), crime (which madegiant), as human well as the teaching of ethics (human relation ship with God and man's relationship with the/other creatures). Ramayana comic masterpiece by R.A. Kosasih is presented as a whole and trim, as well as unique, both in narrative and in the comic depscription techniques.